Journalism, media and technology predictions 2016 - Newman, N (Reuters Institute for the Study of Journalism, 2016)
This year’s key developments will centre on online video, mobile apps and further moves towards distributed content. Mounting problems around online display advertising will lead to a burst of innovation around journalism business models.